(untitled) (Sustainability in Debate, 2023)
This study addresses the social and environmental repercussions on Amazonian communities due to gold mining following the conclusion of official concessions. Framed within the literature on natural resource extraction, sustainability, and social impacts in developing countries, the work employs qualitative methods, including interviews with residents and field observations in the community of Yutzupino in the Ecuadorian Amazon. It reveals that post-concession mining, often informal and illegal, sharply triggers social and environmental degradation. The research emphasises the need to incorporate sustainability principles into mining concessions to prevent such effects. This analysis enhances understanding of the complex socio-ecological aftermath of mining in vulnerable environments. It proposes recommendations for mitigation, underlining the importance of dialogue between communities, governments, and mining companies.